Shallot Agrotourism Based on Local Resources (Mulch and Organic Fertilizer) to Achieve Sustainable Agroecosystem in Sigerongan Village - A. Farid Hemon; Tufaila Hemon; Endah Wahyuningsih; Lestari Ujianto; Dwi Putra Buana Sakti (Pascasarjana Universitas Mataram, 2025)
The Farming in Sigerongan village is highly intensive, potentially leading to chemical residues such as pesticides and fertilizers, which pose a problem for the biological, physical, and chemical balance of the soil and the environment. Sigerongan village, with its